APPLICATION OF MOTIVATIONAL INTERVIEWS IN THE SCOPE OF HEALTH: INTEGRATIVE REVIEW - Silva, Alicyregina Simião (2022)
Motivational Interviewing (MI) is considered an important educational technology implemented in the care practice of health professionals, with the aim of helping to empower the population, in addition to contributing to a better bond between professional and patient. Therefore, the objective is to identify in the scientific literature the way in which MS is used in the context of Nursing. This is an Integrative Literature Review, based on the question “What scientific evidence exists about the implementation of MI in the Nursing Context?”. The research was carried out in the LILACS, Pubmed, Web of Sciene and Cinahl databases, using the descriptors Nursing/Nursing and Motivational Interviewing/Motivational Interviewing, with studies from 2016 to 2021. Data collection and analysis was performed from the reading of titles, abstracts and full texts of scientific articles. The final study sample consisted of 19 articles. It was observed that MS is a technology used in different contexts that encompass health, in which the monitoring of patients with chronic diseases stands out. Regarding the mode of application of the technology, a preference for the face-to-face approach was observed, being performed in most studies in a hospital environment. The results also showed that MS is an effective technology in promoting individual autonomy and improving health standards. It is concluded that MS is important and necessary for a holistic and integral health care, aiming, above all, to guarantee the community's autonomy over the health-disease process.